Molecular evidence of the inhibitory potential of melatonin against sodium arsenite toxicity - Ramtin Farhadi; Marzieh Daniali; Maryam Baeeri; Reza Khorasani; Hamed Haghi-Aminjan; Mahdi Gholami; Mahban Rahimifard; Mona Navaei-Nigjeh; Mohammad Abdollahi (Heliyon)
Introduction: Sodium arsenite (SA), NaAsO2, is among the most hazardous toxicants, and wide use and presence of this toxicant leads to a severe environmental threat. Exposure to SA is associated with many health concerns, such as the prevalence of cancer and diabetes mellitus type 2 (DMT2). Many studies suggest that SA induces inflammation and biochemical impairments through different mechanisms, including increasing oxidative stress and altering vital genes such as biochemical and anti-inflammatory. Recent studies on melatonin (MLT), a harmless hormone secreted in the body generally for induction of sleepiness, find many beneficial and positive effects. Mitigating different harms and toxicities through different mechanisms, such as antioxidant properties, anti-inflammatory effects, and critical gene regulation, is essential. Due to these findings, this study aimed to evaluate the hypothesis that MLT may ameliorate pancreatic damage caused by exposure to SA. Methods: Forty-eight adult healthy male wistar rats aged 7–8 weeks were divided into eight for this research. Group 1 did not receive any intervention. Group 2 received 10 mg/kg/day MLT through intraperitoneal (IP) injection. Groups 3, 4, and 5 received 1.5 (1/10 LD50), 5 (1/3 LD50), and 7.5 (1/2 LD50) mg/kg SA, respectively. Groups 6, 7, and 8 were given 1.5 (1/10 LD50), 5 (1/3 LD50), and 7.5 (1/2 LD50) mg/kg of SA along with 10 mg/kg/day MLT, respectively, during the last ten days of the experiment. After 28 days of the experiment, the blood and tissue samples of the pancreas were removed for biochemical and pathological examination. Results: MLT attenuates SA toxicity by reducing oxidative stress biomarkers and inflammation markers. Moreover, MLT improves SA exposure's biochemical and functional damages by regulating related genes and pathways. Conclusion: MLT poses protective and preventive effects on the pancreas against exposure to SA. However, MLT's therapeutic and beneficial impacts have great potential for further investigation.